1981
DOI: 10.1093/brain/104.4.647-a
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Control in Macaque Monkeys

Abstract: We carried out experiments on young adult macaque monkeys (M.fascicularis) in an attempt to establish whether or not primates possess a locomotor control system consisting of spinal pattern generators modulated by brain-stem locomotor regions. We could not induce 'spinal stepping' in our subjects after spinal cord transection. Sparing of pathways contained in the central sector of the white matter of the cord was sufficient for stepping and walking. 'Controlled locomotion' was elicited in thalamic monkeys by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(72 citation statements)
references
References 3 publications
3
69
0
Order By: Relevance
“…Similar spinal organisations have been suggested in primates, but their activation under experimental conditions is more difficult than in other animal species, suggesting a stronger supraspinal control onto the presumed spinal step generators in primates [16,17]. Besides clinical observations in patients with spinal cord injury or cortical lesion, experimental data obtained in neurologically intact subjects further support the crucial role of motor cortex in human locomotion [6,9,18].…”
Section: Discussionsupporting
confidence: 69%
“…Similar spinal organisations have been suggested in primates, but their activation under experimental conditions is more difficult than in other animal species, suggesting a stronger supraspinal control onto the presumed spinal step generators in primates [16,17]. Besides clinical observations in patients with spinal cord injury or cortical lesion, experimental data obtained in neurologically intact subjects further support the crucial role of motor cortex in human locomotion [6,9,18].…”
Section: Discussionsupporting
confidence: 69%
“…This has been demonstrated on a treadmill in decerebrate models of the cat 14 the rat, 15 and also to some extent, in the primate. 16 It has been shown, in anaesthetized rats, that tonic activity is recorded from nearly three quarters of the neurons (type 2) in the PPN and bursting patterns are seen in a quarter (type 1). 17 It has been postulated that the tonic neurons control the duration of the stepping movements, while the bursting neurons modulate the frequency.…”
Section: Anatomy and Connections Of The Ppnmentioning
confidence: 99%
“…Eidelberg et al [9] have demonstrated a form of patterned locomotion with stimulation of the mesencephalic locomotor region, an area near the nucleus cuneifomis below the superior cerebellar peduncle. This area includes the pedunculopontine nucleus (PPN), which is a good candidate for a locomotor center.…”
Section: Anatomy and Physiologymentioning
confidence: 99%